Retained bronchial foreign body diagnosed after 29 years of penetrating chest trauma - Rimal, Ankit; Pun, Bishika; Karki, Bipin; Paudel, Ashmita; Pradhan, Utsav Lal; Shrestha, Pramesh Sunder (Nepalese Respiratory Journal, 2022)
This is a case of retained bronchial foreign body identified by Computed Tomography (CT) scan after 29 years of initial penetrating chest trauma. The patient had a long-standing history of shortness of breath which was diagnosed and treated as recurrent pulmonary infections. The case report is an attempt towards eliciting the importance of CT scan in identifying such foreign bodies. Interpretation & diagnosis of long standing organic foreign bodies may present with occasional diagnostic dilemma. However, prompt and accurate diagnosis is necessary to prevent complications that can be serious and, as in our case, potentially fatal.